Two-level friction damping and its application for passive multi-functional vibration control of high-rise buildings. (15th July 2021) - Friis, Tobias; Katsanos, Evangelos I.; Saberi, Mogens; Koss, H. Holger H.
Highlights: The paper investigates the performance of a dynamic system with a passive two-level friction damper. The damper is demonstrated for mitigation of both wind- and earthquake-induced vibration of a high-rise building. The performance is evaluated in comparison with the conventional one-level friction damper. The two-level friction damper is found to have an extended amplitude range of optimal performance compared to the conventional one. The paper contains detailed description of how to simulate systems with this damper type. Abstract: In recent years, the use of structural elements and/or entire structures with low internal damping are favoured with the increasing trend for unconventional design of structures and infrastructures that combine high functionality and increased aesthetics. One example is the advancement of high-rise buildings, which are built taller, more slender and with more spectacular designs compared to the past. In many of these cases, supplementary damping is included in the structural design by installing distributed passive damping devices, among which the friction damper has become popular due to its relative low cost, high reliability and high efficiency. The conventional friction damper, however, can only mitigate vibrations optimally with respect to a single deformation shape at a single vibration amplitude, which is not enough in cases where additional damping is required to mitigate different magnitudes of the excitation. Thus, the paper scrutinises the performance of the passive two-level friction damper, recently proposed elsewhere, in comparison to the conventional one-level friction damper, and assesses its application for multi-functional vibration control of a high-rise building. Specifically, this paper scrutinises the application and performance of the two-level friction damper in two simulation-based frameworks and ultimately: (i) evaluates and demonstrates the vibration performance of a dynamic system when equipped with this damper type, and (ii) investigates the application of this damper type for mitigation of both wind- and earthquake-induced vibration of a high-rise building. It is found that the optimal performance of the two-level friction damper is covering a larger vibration amplitude range compared to the conventional friction damper, which enabled the two-level friction damper to, in contrast to the conventional friction damper, successfully mitigate both wind- and earthquake-induced vibration in the application example. Based on the findings, it is concluded that the two-level friction damper is able to overcome some of the limitation, application-wise, connected to the amplitude dependence of the one-level friction damper.